KOMUNIKASI ANTAR AKTOR DALAM IMPLEMENTASI KEBIJAKAN MASJID PARIPURNA DI KOTA PEKANBARU - Riauwati, Raja Hazrulan; As’ari, Hasim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The Paripurna Mosque is a Pekanbaru City policy made to realize the Vision and Mission of Pekanbaru City. In implementing this policy, there are problems in communication between actors. What happens to the direct and indirect actors of this policy. Mayor of Pekanbaru, People's Welfare (KESRA) of Pekanbaru City, Administrators of the Plenary Mosque from the City, Subdistrict, and Sub-District levels as well as members of the Paripurna Mosque participate in the policy. The problem that occurs is that there is still a lack of communication coordination between actors which makes implementers feel confused in implementing policies.Â The purpose of this research is to find out how communication and the obstacles that occur to the actors implementating this policy. The theory used is George Edward III Theory, namely 3 communication criteria, namely Transmission, Clarity, and Consistency. This research method uses qualitative methods as descriptive research in the form of in-depth written and oral data. The informants were taken by purposive sampling technique, namely the sampling technique with certain considerations. The research method uses interview observation and documentation.Â The results of this study indicate that communication between actors in the implementation of the plenary mosque policy in Pekanbaru City is still ineffective because in the distribution of information to actors there are still obstacles such as human resources who are not adept at conveying information so that detailed information is not channeled to implementers. the lack of coordination in checking the overall Masjid Paripurna, as well as the limited means of communication on policy implementers and those who cover it.Keywords: Communication, Transmision, Clarity, and Consistent